Bibliometric analysis of multiple criteria decision making in agriculture - Francik, Sławomir; Pedryc, Norbert; Knapczyk, Adrian; Wójcik, Artur; Francik, Renata; Łapczyńska-Kordon, Bogusława (Technical Sciences, 2016)
Development trends (Research Trends) in scientific research on the methods of Multiple Criteria Decision Making (MCDM) and Multiple Criteria Decision Analysis (MCDA) in agriculture are analyzed. Established bibliometric techniques are applied. MCDA/MCDM methods are being very intensively developed in recent years, as evidenced by the number of scientific papers published annually in renowned scientific journals indexed in the Web of Science (WoS) database. In the years 1979-2015 a total of 1,355 scientific articles were collected in the database. The number of articles published annually increased rapidly after 2005. Besides, the annual number of citations of the publications is increasing. Research on MCDA/MCDM is conducted in many research areas. In the years 1984-2015 the Web of Science database accumulated 27 scientific publications on MCDA/MCDM in agriculture area. Therefore, it can be concluded that the MCDA/MCDM issues are currently not sufficiently analyzed in relation to agriculture. In the future this subject will probably be further developed, an increasing number of scientists will conduct research on the MCDA/MCDM and the annual number of articles published in the field will increase.